Three new species of Tomocerus from tropical zone of China (Collembola, Tomoceridae) - Yu, Daoyuan; Yang, Xiaodong; Liu, Manqiang (Zootaxa, 2018)
Tomocerids are world-widely distributed, but were seldom reported from tropics. In the present paper, three new species of Tomocerus Nicolet are described from Hainan and Yunnan Provinces, tropical zone of China. All three species have compound-type dental spines and belong to Tomocerus ocreatus species-group. Tomocerus tropicus sp. nov. resembles Tomocerus pseudocreatus Yu, but differs from the latter in mesothoracic macrochaetotaxy, manubrial dorsal scales and denticles on the dental spines. Tomocerus nan sp. nov. resembles Tomocerus virgatus Yu, but differs from the latter in colour pattern, cephalic dorsal macrochaetotaxy, manubrial dorsal scales and denticles on the dental spines. Tomocerus nabanensis sp. nov. resembles T. postantennalis Yu, Zhang & Deharveng, Tomocerus dong Yu & Li and Tomocerus deharvengi Yu & Li, but differs from the three species in PAO, cephalic and tergal dorsal macrochaetotaxy and tenent hairs. Our studies including the present work indicate the importance of future survey on Tomocerinae in and near tropics where diversity of this group was historically underestimated.